Constructions of Decision Making for Risk-Reducing Mastectomy. (August 2018) - Graham, Ruth; Owens, Marilyn; Priest, Helena; Hutton, Stephanie
This research article explores constructions of the decision-making process for risk-reducing mastectomy and considers the consequent role and responsibility of clinical psychologists. Using a Foucauldian discourse analysis approach, three online newspaper articles, five online forums, and four semi-structured interviews were analyzed. Seven discursive constructions are identified and discussed within three broader discourses of mental illness, risk, and embodied selves. Primary conclusions highlight the role for clinical psychologists and health professionals to incorporate the multiple social and political factors involved in discourses that shape decision making. The role of power is critically considered and there is a need for further analysis of "talk" among health professionals.